Bike paths to nowhere. Bicycle infrastructure that ignores the street network. - Fleming, Steven (Routledge, 2018)
In the article the term "cycle space" is used to describe the worlds cyclist build around themselves with clothing, accoutrements, sometimes architecture and invariably safe routes through cities. Cognitively and actually cycle space is built to attain an own sense of fulfillment and safety as cyclists. Working through the five elements that according to Lynch define our images of our cities, that "path" can be generalized in the minds of most cyclists would incorporate a few easements corresponding to former bulk haulage routes; that "edges" for cyclists are less likely to be shoplined than lined with blank walls, graffiti, and wire fences; that cyclists' "districts" could include derelict zones that meither industry nor mainstream car-dependent society are actively contesting; that bike riders' "nodes" will have no markers put there by governments; and that something like a culvert section under a highway is more likely to be a "landmark" for cyclists than any civic monument or sign of commerce.
Keywords: Fahrradinfrastruktur; Stadtplanung; Raumplanung; Fahrradverkehr; Fahrradweg; Radwegenetz; Radwegeplanung; Straßennetz; Routenplanung